Predicting the clustering properties of galaxy clusters detectable for the Planck satellite - Moscardini, Lauro; Bartelmann, Matthias (Arxiv, 2013)
We study the clustering properties of the galaxy clusters detectable for the Planck satellite due to their thermal Sunyaev-Zel'dovich effect. We take the past light-cone effect and the redshift evolution of both the underlying dark matter correlation function and the cluster bias factor into account. A theoretical mass-temperature relation allows us to convert the sensitivity limit of a catalogue into a minimum mass for the dark matter haloes hosting the clusters. We confirm that the correlation length is an increasing function of the sensitivity limits defining the survey. Using the expected characteristics of the Planck cluster catalogue, which will be a quite large and unbiased sample, we predict the two-point correlation function and power spectrum for different cosmological models. We show that the wide redshift distribution of the Planck survey, will allow to constrain the cluster clustering properties up to z=1. The dependence of our results on the main cosmological parameters (the matter density parameter, the cosmological constant and the normalisation of the density power-spectrum) is extensively discussed. We find that the future Planck clustering data place only mild constraints on the cosmological parameters, because the results depend on the physical characteristics of the intracluster medium, like the baryon fraction and the mass-temperature relation. Once the cosmological model and the Hubble constant are determined, the clustering data will allow a determination of the baryon fraction with an accuracy of few per cent.